Revisiting substance P in migraine: a methodological approach inspired by anti-CGRP and anti-PACAP success - Lanfranco Pellesi; Lars Edvinsson (The Journal of Headache and Pain)
Abstract Substance P, previously dismissed as a therapeutic target for migraine due to the failure of neurokinin-1 receptor antagonists, warrants renewed attention. Building on the success of therapies targeting the calcitonin gene-related peptide (CGRP) system and pituitary adenylate cyclase-activating peptide (PACAP) in migraine prevention, which highlight the importance of targeting peptides, this proposal reexamines substance P as a mediator in migraine pathophysiology. Using an established methodological framework, migraine-inducing properties of substance P can be evaluated through randomized, double-blind, placebo-controlled crossover studies involving healthy volunteers and individuals with a history of migraine. This approach aims to establish proof of concept for substance P’s role in migraine, laying the groundwork for investigations with animal and cell-based models and advancing the development of innovative treatments for patients refractory to current therapies.